2019
DOI: 10.3390/ani9100713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Low-Protein Diet on Microbiota Structure and Function in the Jejunum of Huzhu Bamei Suckling Piglets

Abstract: Simple SummaryIn mammals, the intestine is the main organ where nutrients are digested and absorbed, thus serving a central role in the growth and health of animals. Low-protein diets are based on the “ideal amino acid” theory, where AA crystals are added to ensure the amino acid balance of the diet. As a result, the amino acid nutritional needs of piglets are reduced along with the total protein level of the diet as well as the metabolic burden of piglets. This typically results in reduced diarrhea and improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…The specific steps were reported in previous research studies [54], total bacteria DNA was extracted from the jejunum content samples using the PowerSoil® DNA Isolation Kit (MO BIO Laboratories, Inc., Carlsbad, CA, USA) according to the manufacturer's instruction, and was stored at − 80°C until the time of analysis. Sequencing of the16S rRNA gene was outsourced to BIOMARKER (Beijing, China).…”
Section: S Rrna Gene Sequencing and Kegg Analysismentioning
confidence: 99%
“…The specific steps were reported in previous research studies [54], total bacteria DNA was extracted from the jejunum content samples using the PowerSoil® DNA Isolation Kit (MO BIO Laboratories, Inc., Carlsbad, CA, USA) according to the manufacturer's instruction, and was stored at − 80°C until the time of analysis. Sequencing of the16S rRNA gene was outsourced to BIOMARKER (Beijing, China).…”
Section: S Rrna Gene Sequencing and Kegg Analysismentioning
confidence: 99%
“…Studies have shown that for every 1% reduction of CP in pig diet, nitrogen emissions can be reduced by 8% to 10%, and ammonia concentration in pig houses can be reduced by more than 10% [5]. In the case of supplementation of important EAA, a reduction of 2% to 3% in dietary CP content did not affect the nitrogen deposition or growth performance of pigs [6,7], but the growth performance of pigs was usually negatively affected when the dietary CP content was more than 3% [5,8]. The increasingly serious environmental pollution forces researchers to fundamentally solve the protein and amino acid nutrition of pigs while reducing the nitrogen excretion of pig feces.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for this might be microbiota. Early postnatal life is a curial time for immune system development [38]. During early postnatal period, host-microbiota interactions in uence the development of the host immune system, muscle and other tissues [39][40][41].…”
Section: Discussionmentioning
confidence: 99%